Crown Ether‐Assisted Growth and Scaling Up of FACsPbI3 Films for Efficient and Stable Perovskite Solar Modules. (21st December 2020) - Chen, Ruihao; Wu, Yazhuo; Wang, Yongke; Xu, Ruchao; He, Ruiqin; Fan, Yangtao; Huang, Xiaofeng; Yin, Jun; Wu, Binghui; Li, Jing; Zheng, Nanfeng
Abstract: FACs‐based (FA +, formamidinium and Cs +, cesium) perovskite solar cells have gained great attention due to their remarkable light and thermal stabilities toward practical application of perovskite modules. However, the moisture instability and difficulty in scalable fabrication are still the main obstacles blocking their photovoltaic applications in current status. Here, the employment of novel interaction between crown ether with metal cations is introduced to tailor the uniform growth and inhibit moisture invasion during the crystallization of α‐phase FACsPbI3, yielding the successful synthesis of high‐quality perovskite films in a large scale. Consequently, perovskite solar cells (PSC) modules in the total area of 4 × 4 and 10 × 10 cm 2 are readily fabricated with respective champion efficiencies of 16.69% and 13.84% and excellent stability over 1000 h. This facile scaling‐up strategy assisted by crown ether has shown great promise for pursuing efficient and highly stable large‐area PSC modules. Abstract : Moisture instability and unscalable fabrication protocols remain unsolved issues that hinder the application of FACs‐based perovskite solar cells. Here, high‐quality FACsPbI3 films are fabricated by crown ether tailoring (which chelated with Cs + /Pb 2+ ions) to inhibit the moisture invasion and stabilize the a ‐phase FACsPbI3, producing large‐area perovskite films and with solar module performance.